2022
DOI: 10.1186/s13014-022-02004-7
|View full text |Cite
|
Sign up to set email alerts
|

Response assessment after stereotactic body radiation therapy for spine and non-spine bone metastases: results from a single institutional study

Abstract: Background The use of stereotactic body radiation therapy (SBRT) for tumor and pain control in patients with bone metastases is increasing. We report response assessment after bone SBRT using radiological changes through time and clinical examination of patients. Methods We analyzed retrospectively oligo-metastatic/progressive patients with bony lesions treated with SBRT between 12/2008 and 10/2018, without in-field re-irradiation, in our instituti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Open surgical treatment, which consists of decompressive laminectomy with longlevel screw fixation and bone fusion, is indicated in cases of obvious spinal instability, clinically significant neural compression secondary to retropulsed posterior somatic wall or spinal deformity, intractable pain unresponsive to nonsurgical measures, and radiotherapy failure, but it is often of limited benefit in the management of spinal metastases due to its morbidity [2]. Some histological forms of bone metastases, such as those arising from sarcoma, renal cell carcinoma, non-small cell lung carcinoma, and melanoma, respond less well to radiotherapy [16]. Furthermore, the use of radiotherapy is limited by spinal cord cumulative dose tolerance [17].…”
Section: Discussionmentioning
confidence: 99%
“…Open surgical treatment, which consists of decompressive laminectomy with longlevel screw fixation and bone fusion, is indicated in cases of obvious spinal instability, clinically significant neural compression secondary to retropulsed posterior somatic wall or spinal deformity, intractable pain unresponsive to nonsurgical measures, and radiotherapy failure, but it is often of limited benefit in the management of spinal metastases due to its morbidity [2]. Some histological forms of bone metastases, such as those arising from sarcoma, renal cell carcinoma, non-small cell lung carcinoma, and melanoma, respond less well to radiotherapy [16]. Furthermore, the use of radiotherapy is limited by spinal cord cumulative dose tolerance [17].…”
Section: Discussionmentioning
confidence: 99%
“…A common pitfall in post SBRT imaging is the phenomenon of pseudoprogression. This occurs when there is a significant increase in post-treatment lesion volume usually without significant clinical symptoms, with eventual stabilization or regression on subsequent imaging [117,151]. This is well documented in the brain, lung and liver [117].…”
Section: Post-treatment Follow-upmentioning
confidence: 99%
“…However, more research may be needed as a recent case report demonstrated a patient with pseudoprogression in the form of an epidural mass [156]. The timeframe is also important, with pseudoprogression occurring within a few weeks up to 6 months post SBRT, in contrast to the late presentation of radio-necrosis which may occur years after therapy [151]. Growth confined within the 80% prescription isodose-line and lytic lesions (as opposed to sclerotic lesions) have also been shown to be predictive of pseudoprogression [155,157].…”
Section: Post-treatment Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The only major difference is that review studies have found that patients receiving single-fraction treatment have a higher incidence of requiring re-irradiation [ 11 ]. The efficacy of radiation in achieving pain control has also been found to hold true with the utilization of SBRT [ 41 ].…”
Section: Evidence For Post-operative Radiotherapy In Non-spine Bone M...mentioning
confidence: 99%